Bombyx mori transgenic lines for the induction of constitutive dsRNA interference of the clock gene period (Bollettino di zoologia agraria e bachicoltura, 2024)
The circadian clock of insects consists of interlocking transcriptional feedbackloops which are positively and negatively regulated by the complex interaction ofa number of "clock" genes and their protein products. One of these genes, period(per), plays a central role in the core of the circadian oscillator of the dipteranDrosophila melanogaster. Mutations in this gene lead to alterations in circadianrhythmicity and developmental timing. In order to establish whether similar effectscan also be observed in other insects, we employed a construct suitable for theembryonic transformation of the lepidopteran Bombyx mori. This construct wasengineered to allow specific ds RNA interference-induced post-transcriptionalgene silencing of the Bombyx per gene. A preliminary molecular characterizationof the resulting transformants shows that several independent transgenic linesharboring variable numbers of transgenes were obtained.
Keywords: Bombyx mori; clock genes; transgenesis; dsRNA interference; posttranscriptional gene silencing